LEMBAGA PEMASARAN BERAS DI KABUPATEN TANGGAMUS - Fadilah, Suci; Trisnanto, Teguh Budi; Apriyani, Marlinda (Universitas Galuh, 2023)
Marketing distribution describes the distribution chain of a commodity from producers to final consumers to an area that involves a trading activity. The more marketing agencies that are involved in the marketing of products, the lower the price that will be received by the producers. This study aims to describe marketing channels and analyze actors in marketing institutions in Tanggamus Regency. Sampling was determined by the snowball method (snow ball sampling). The marketing agency informants in this study consisted of 35 producer informants, 30 agent informants and 35 retailer informants. The data analysis technique used in this research is descriptive analysis technique. The results showed that there were 3 marketing channels in Tanggamus Regency, namely: 1. Channel I: Producers - Consumers, 2. Channels II: Producers - Agents - Consumers, 3. Channels III: Producers - Agents - Retailers - Consumers. Actors in marketing institutions in Tanggamus Regency consist of producers, agents, retailers and consumers. Producers are farmers who sell their rice to agents or directly to consumers. Agents are collectors and rice mills that collect rice from producers (farmers), which will later be resold to retailers or directly to consumers. Retailers are traders who sell the goods they sell directly to end users or end consumers in unit or retail quantities. The intended consumers in this study are people who buy and consume rice in Tanggamus Regency.